Reform of criminal Code and Requirements building of Good Governance - Isa, Hassan Abd-Ali (Journal of University of Human Development, 2016)
The law is a key input for the establishment of good governance, it is no guarantee the rule of law cannot achieve good governance in the community requirements. So the law must be responsive to the objectives which aims to achieve good governance on the one hand, and the line with the social, economic and political transformations concurrent with his other hand. This dialectical relationship assumes without doubt the various branches of law reform, including the Iraqi Penal Code No. 111 of 1969. The purpose statement that includes research on two aspects, the first focuses on clarifying dialectical relationship between good governance and reform of the Penal Code. The second shows the main directions of the reform of the Iraqi Penal Code No. 111 of 1969, with a focus on the most important, in the light of contemporary criminal policy. It is limited to the (humanization of the criminal law), and (expand criminalization circle), and (internationalization of the criminal law).